سامی ادیان میں تصوف کے تصورات اور تجربات کا تقابلی جائزہ: Conception and experiences of Mysticism in Semitic religions A Comperative review - Shehzadi, Saima; Bukhari, Dr. Syed Hamid Farooq (Al-Irfan, 2023)
Spiritual experiences and the attainment of enlightment had been a favorite subject and spiritual need of humanities since day first. This article examines the experiences and core beliefs of mysticism in semitic religions in narrative and analytical style. Man goes to great lengths to gain power and success in social affairs, but the other side of the picture is that, arrangements for the peace of the soul in could not attain by aristocratic life style. It is fact that history is not unfimiliar with the experience and statements of sufism. A group of people striving for spiritual perfection has its special position in the history of religions. The characteristics of semistic religions is their rightful claim, that is, ALLAH gave these religion a unique from other religions. Then, in his last book the Holy Quran, he mentioned the habits, beliefs, religious and spiritual experiences and faith of these religions in detail compared to other religions. This research will present a comparative analysis of mystic experience, status, styles, aims of austerity, and tradition of spiritual experiences in semitic religions. Hence, the similarities and differences.